Fluorosulfonic acid resins and their preparation methods, membrane electrode assemblies

CN122978342APending Publication Date: 2026-10-27HUAIROU LABORATORY SCIENCE & TECHNOLOGY ACHIEVEMENTS TRANSFORMATION CENTER HUAIROU DISTRICT BEIJING
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611471101.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-21
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0007]本发明的目的是为了克服现有技术存在的高透氧树脂结构单一、力学性能差、透气性提升有限问题,提供一种含氟磺酸树脂及其制备方法、膜电极接合体及其应用

Benefits of technology

1、本发明的树脂具有低传质阻抗、高气体透过率,并且氧气在本发明的树脂中具有良好的溶解度,因此可以进一步加强气体透过效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978342A_ABST
    Figure CN122978342A_ABST
Patent Text Reader

Abstract

This invention relates to the field of fluorosulfonic acid resin technology, specifically disclosing a fluorosulfonic acid resin, its preparation method, and a membrane electrode assembly. The fluorosulfonic acid resin comprises a first repeating unit as shown in Formula I, a second repeating unit as shown in Formula II, and a third repeating unit as shown in Formula III; Formula I; Formula II; Formula III; wherein R1, R2, R3, and R4 are each independently F or C1-C7 straight-chain or branched fluoroalkyl groups; R5, R6, R7, and R8 are each independently F or C1-C3 fluoroalkyl groups; at least one of Y or Z is S, n is 1 or 2, and m is 0 or 1; R9, R... 10 Each component is independently a fluorinated alkyl group of F or C1-C3; w is an integer from 0 to 5, v is an integer from 0 to 5, w and v are not both 0, X is F, Cl or OM; M is H or an alkali metal. This fluorosulfonic acid resin has good air permeability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fluorosulfonic acid resin technology, specifically to a fluorosulfonic acid resin and its preparation method, and a membrane electrode assembly. Background Technology

[0002] Proton exchange membrane fuel cells and water electrolysis for hydrogen production are core technologies in the hydrogen energy industry. Membrane electrode assemblies (MEAs), as core components, typically have catalyst layers composed of platinum, iridium, and other precious metal catalysts combined with perfluorosulfonic acid ionomers. Currently, the industry aims to reduce costs by decreasing the amount of precious metals used; however, reducing catalyst usage exacerbates mass transfer polarization, leading to a decline in device performance. Simultaneously, high-power applications demand higher current density operation, making the gas mass transfer resistance of the catalyst layer a key bottleneck restricting performance improvement.

[0003] Traditional perfluorosulfonic acid resins have a dense structure, which can effectively block gases at both electrodes when used in proton exchange membranes. However, in catalyst layers, they tightly encapsulate the catalyst, forming a dense nanofilm that significantly increases local gas mass transfer resistance. Existing technologies often add pore-forming agents to optimize mass transfer, but this requires additional water washing and heat treatment. Residual byproducts affect catalyst layer performance, and large pore sizes can disrupt proton conduction continuity. Although the industry has prepared high-oxygen-permeable ionomers by introducing cyclic structures into the main chain to improve oxygen permeability, these resins have simple structures, poor chemical stability, or limited oxygen permeability improvement, failing to balance proton conduction, oxygen transport, and long-term durability, making them unsuitable for the demanding operating conditions of catalyst layers in both types of devices. Therefore, developing a dedicated perfluorosulfonic acid resin with high oxygen permeability and high stability is key to overcoming the current technological bottlenecks.

[0004] CN118994463A discloses a high oxygen permeability resin, its preparation method, and a membrane electrode assembly (MEA) for use in fuel cell catalyst layers. The resin molecule contains a 2,2,4-trifluoro-5-(trifluoromethoxy)-1,3-dioxane cyclic structure and can incorporate sulfonic acid groups. It contains only C, O, and F atoms, lacking heteroatoms susceptible to free radical attack, and exhibits strong chemical stability. This cyclic structure enhances molecular chain rigidity and interchain free volume, increasing oxygen transport channels and improving oxygen permeability. Using this resin to fabricate a MEA can reduce oxygen mass transfer resistance and improve the power density of low-platinum MEAs at high current densities, making it suitable for industrial applications in fuel cells. However, the resin's improvement in oxygen permeability is limited, its formulation tolerance is low, and its application scenarios are restricted. It is only suitable for low-platinum MEAs in fuel cells, resulting in a narrow applicability and insufficient versatility.

[0005] CN118085155A discloses a perfluorinated ionomer with high oxygen permeability and weak adsorption, its preparation method, and its application in fuel cells. The method involves free radical copolymerization of a perfluorodioxane cyclic monomer and a perfluorosulfonyl fluoride monomer, followed by nucleophilic substitution to prepare a sulfonylimide resin, and then protonation to obtain the target ionomer. Containing sulfonylimide groups, it exhibits strong proton dissociation, good low-humidity performance, weak Pt adsorption, and its cyclic structure enhances oxygen permeability, which can improve the high-current mass transfer polarization of fuel cells. However, the resin backbone is rigid, lacks flexibility, and is difficult to disperse; the nucleophilic substitution and protonation processes have poor controllability, making it difficult to guarantee product purity and batch consistency; the sulfonylimide groups have poor chemical stability, limiting its application scenarios and making it difficult to cope with complex and fluctuating operating conditions such as water electrolysis for hydrogen production, thus lacking versatility.

[0006] In summary, existing high-oxygen-permeable resins suffer from problems such as simple structure, poor mechanical properties, poor chemical stability, and limited improvement in air permeability. They cannot simultaneously achieve proton conduction, oxygen transport, and long-term durability, making them unsuitable for the demanding operating conditions of catalyst layers in both types of devices. Therefore, developing a dedicated perfluorosulfonic acid resin with high air permeability and high stability is key to overcoming the current technological bottlenecks. Summary of the Invention

[0007] The purpose of this invention is to overcome the problems of existing high-oxygen-permeable resins, such as simple structure, poor mechanical properties, and limited improvement in air permeability, and to provide a fluorosulfonic acid resin, its preparation method, a membrane electrode assembly, and its application. This fluorosulfonic acid resin exhibits excellent air permeability.

[0008] To achieve the above objectives, the present invention provides a fluorosulfonic acid resin, wherein the fluorosulfonic acid resin includes a first repeating unit shown in Formula I, a second repeating unit shown in Formula II, and a third repeating unit shown in Formula III; Formula I; Formula II; Formula III; Among them, R1, R2, R3, and R4 are each independently a straight-chain or branched fluorinated alkyl group of F or C1-C7. R5, R6, R7, and R8 are each independently an F or C1-C3 fluoroalkyl group; at least one of Y or Z is S, n is 1 or 2, and m is 0 or 1; R9, R 10 Each is independently an F or C1-C3 fluorinated alkyl group; w is an integer between 0 and 5, v is an integer between 0 and 5, w and v are not both 0, and X is F, Cl or OM; M is H or an alkali metal; a, b, and c represent the number of repeating units, each of which is an integer.

[0009] A second aspect of the present invention provides a method for preparing a fluorosulfonic acid resin, the method comprising: In the presence of an initiator and a solvent, fluorinated monoolefin monomers, fluorinated heterocyclic olefin monomers, and fluorinated sulfonic acid ether monomers are copolymerized to obtain fluorinated sulfonic acid resins. The fluorinated monoolefin monomer includes The fluorinated heterocyclic olefin monomer includes The fluorosulfonic acid ether monomer includes ; Among them, R1, R2, R3, and R4 are each independently a straight-chain or branched fluorinated alkyl group of F or C1-C7. R5, R6, R7, and R8 are each independently an F or C1-C3 fluoroalkyl group; at least one of Y or Z is S, n is 1 or 2, and m is 0 or 1; R9, R 10 Each is independently an F or C1-C3 fluorinated alkyl group; w is an integer between 0 and 5, v is an integer between 0 and 5, w and v are not both 0, and X is F, Cl or OM; M is H or an alkali metal; a, b, and c represent the number of repeating units, each of which is an integer.

[0010] A third aspect of the present invention provides a membrane electrode assembly comprising a proton exchange membrane and a catalyst layer disposed on one side surface of the proton exchange membrane; the catalyst layer comprising a fluorosulfonic acid resin and a catalyst dispersed in the fluorosulfonic acid resin.

[0011] Through the above technical solutions, the fluorosulfonic acid resin and its preparation method, membrane electrode assembly and its application provided by the present invention achieve the following beneficial effects: 1. The resin of the present invention has low mass transfer resistance and high gas permeability, and oxygen has good solubility in the resin of the present invention, thus further enhancing the gas permeability effect.

[0012] 2. The resin of the present invention also has good mechanical properties.

[0013] 3. The resin of the present invention has a wide range of applications, including catalyst layer ionomers for fuel cells and catalyst layer ionomers for hydrogen production by water electrolysis. Attached Figure Description

[0014] Figure 1 These are the X-ray scattering curves of the resins in Example 1, Comparative Example 1, and Comparative Example 3. Detailed Implementation

[0015] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0016] In order to solve the problems existing in the prior art, the first aspect of the present invention provides a fluorosulfonic acid resin, comprising a first repeating unit shown in Formula I, a second repeating unit shown in Formula II and a third repeating unit shown in Formula III. Formula I; Formula II; Formula III; Among them, R1, R2, R3, and R4 are each independently a straight-chain or branched fluorinated alkyl group of F or C1-C7. R5, R6, R7, and R8 are each independently an F or C1-C3 fluoroalkyl group; at least one of Y or Z is S, n is 1 or 2, and m is 0 or 1; at least one of Y or Z is S. R9, R 10 Each is independently an F or C1-C3 fluorinated alkyl group; w is an integer between 0 and 5, v is an integer between 0 and 5, w and v are not both 0, and X is F, Cl or OM; M is H or an alkali metal; a, b, and c represent the number of repeating units, each of which is an integer.

[0017] Through research, the inventors discovered that the three structural units selected in this invention have a synergistic effect, thus achieving a significant improvement in air permeability. Through the molecular structure design of this invention, a fluorosulfonic acid resin possessing good mechanical properties, proton conductivity, and air permeability can be obtained. Regarding air permeability, this invention mainly describes it in terms of oxygen permeability; those skilled in the art will understand that this does not mean that the air permeability of the resin of this invention is limited to oxygen permeability.

[0018] In particular, the selection of the first and second repeating units in this invention is especially advantageous for obtaining a fluorosulfonic acid resin with high air permeability. Although the full mechanism cannot be fully elucidated at present, the inventors speculate that this is because, in addition to providing the resin with excellent mechanical strength, the first repeating unit also has a synergistic effect with the heterocyclic structure of the second repeating unit specifically selected in this invention.

[0019] Traditional heterocyclic structures in the prior art, such as five-membered dioxinoxanes containing only O heteroatoms, offer limited permeability when incorporated into fluorosulfonic acid resins. However, this invention, through systematic research, has discovered that sulfur-containing heterocycles can significantly improve permeability. The second repeating unit of this invention provides a sulfur-containing heterocyclic structure to the main chain. This special cyclic structure exhibits good rigidity and provides excellent permeability to the resin. The second repeating unit selected in this invention can reduce mass transfer impedance and improve electrolytic cell / battery efficiency. Furthermore, the heteroatoms of the second repeating unit can weakly interact with O2, forming transient charge-transfer complexes that increase the solubility of oxygen in the polymer, thereby further enhancing permeability.

[0020] The third repeating unit contains a -SO2X group. When it is -SO3H, it can provide proton conduction sites for the resin, thereby increasing the ion exchange capacity and proton conductivity of the resin. Those skilled in the art will also understand that when -SO2X is not SO3H, these groups can be converted to -SO3H through methods commonly used in this technical field; for example, it can be converted through acidification.

[0021] In this invention, if m is 0, then Z is S. That is, the second repeating unit of this invention must contain S.

[0022] In some preferred embodiments of the present invention, three of R1, R2, R3, and R4 in Formula I are F, and the remaining one is a C1-C4 straight-chain or branched perfluoroalkyl group.

[0023] The inventors discovered that by setting R1, R2, R3, and R4 in Formula I to not all be F, thus giving it side chains of a certain length, the free volume in the resin molecular chain can be further increased. In particular, the side chains in the first repeating unit of this invention have a synergistic effect with the heterocyclic structure in the second repeating unit, which can further improve the resin's permeability. If the length of the side chains exceeds the aforementioned preferred range, the permeability will also be affected. Having a certain number of side chains can improve the resin's permeability, but if the number of side chains is too large, the resin's mechanical properties will decrease. Therefore, setting three of R1, R2, R3, and R4 in Formula I to be F is more beneficial for imparting excellent chemical stability and mechanical strength to the resin.

[0024] Preferably, in Formula I, three of R1, R2, R3, and R4 are F, and the remaining one is a C1-C4 straight-chain perfluoroalkyl group.

[0025] In some preferred embodiments of the present invention, m is 1 in Formula II.

[0026] When m is 1, the sulfur-containing heterocycle has better stability.

[0027] In some preferred embodiments of the present invention, m is 1 and n is 1 in Formula II.

[0028] In some preferred embodiments of the present invention, Y and Z in Formula II are both S.

[0029] When both Y and Z are S, the resin has better air permeability.

[0030] In this invention, m is 1 in Formula II, and Y and Z are both S, and the corresponding resin has good air permeability.

[0031] To better promote the synergistic effect of the first repeating unit and the second repeating unit, preferably, in Formula I, three of R1, R2, R3, and R4 are F, and the remaining one is a straight-chain perfluoroalkyl group with C1-C4 carbon atoms; in Formula II, m is 1, and Y and Z are both S.

[0032] In some preferred embodiments of the present invention, R5, R6, R7, and R8 in Formula II are each independently F or CF3.

[0033] The preferred structure described above is more conducive to giving the resin good air permeability, mechanical properties and proton conductivity at the same time.

[0034] In some preferred embodiments of the present invention, in Formula III, w is 0 or 1, and v is 1 or 2.

[0035] Formula III, having the preferred structure described above, possesses suitable side groups that can provide proton conduction sites and also offer greater free volume. In particular, such side groups can further synergize with the preferred side groups in Formula I and the sulfur-containing heterocycles in Formula II, providing better air permeability to the resin of the present invention. When the values ​​of w and v are not within the preferred range, the proton conductivity will decrease.

[0036] More preferably, in formula III, w is 1 and v is 1.

[0037] In some preferred embodiments of the present invention, X in Formula III is OH.

[0038] When X is OH, the resin of the present invention has good ion exchange capacity and proton conductivity.

[0039] In this invention, preferably, R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 All are selected from F or perfluorinated alkyl groups; that is, the fluorosulfonic acid resin is a perfluorosulfonic acid resin, and such perfluorosulfonic acid resin has better chemical stability.

[0040] To adjust the chemical stability, proton conductivity, ion exchange capacity, and air permeability of the resin, the content ratio of each repeating unit can be controlled within a wide range. In some preferred embodiments of the present invention, based on the total weight of the fluorosulfonic acid resin, the content of the first repeating unit is 10-60%, the content of the second repeating unit is 10-60%, and the content of the third repeating unit is 10-70%. Within such a range, especially with the content of the second repeating unit within this range, it is more beneficial to make the resin possess good mechanical properties, proton conductivity, and air permeability.

[0041] Preferably, based on the total weight of the fluorosulfonic acid resin, the content of the first repeating unit is 25-35%, the content of the second repeating unit is 25-40%, and the content of the third repeating unit is 30-50%.

[0042] In some preferred embodiments of the present invention, the perfluorosulfonic acid resin satisfies one or more of the following conditions: The oxygen permeability coefficient tested according to GB / T20042.3-2022 is 11×10⁻⁶. -6 -14×10 -6 cm 3 ·cm / (cm 2 (·s·MPa); The tensile strength, determined according to the method specified in GB / T 20042.3-2022, is 21-24 MPa; The proton conductivity is 110-130 mS / cm.

[0043] A second aspect of the present invention provides a method for preparing a fluorosulfonic acid resin, comprising: In the presence of an initiator and a solvent, fluorinated monoolefin monomers, fluorinated heterocyclic olefin monomers, and fluorinated sulfonic acid ether monomers are copolymerized to obtain fluorinated sulfonic acid resins. The fluorinated monoolefin monomer includes The fluorinated heterocyclic olefin monomer includes The fluorosulfonic acid ether monomer includes ; Among them, R1, R2, R3, and R4 are each independently a straight-chain or branched fluorinated alkyl group of F or C1-C7. R5, R6, R7, and R8 are each independently an F or C1-C3 fluoroalkyl group; at least one of Y or Z is S, n is 1 or 2, and m is 0 or 1; R9, R 10 Each is independently an F or C1-C3 fluorinated alkyl group; w is an integer between 0 and 5, v is an integer between 0 and 5, w and v are not both 0, and X is F, Cl or OM; M is H or an alkali metal; a, b, and c represent the number of repeating units, each of which is an integer.

[0044] The preparation method of this invention starts with raw materials and achieves resin molecular structure design by optimizing monomer selection. It can fundamentally solve the problem of insufficient air permeability of air-permeable resins without the need for subsequent modification and treatment such as adding fillers.

[0045] In some preferred embodiments of the present invention, the copolymerization reaction is carried out at a temperature of 40-120°C, a pressure of 0.1-5 MPa, and a time of 2-48 h.

[0046] Under the above reaction conditions, it is more advantageous to prepare the fluorosulfonic acid resin of the present invention.

[0047] Preferably, the copolymerization reaction is carried out at a temperature of 40-80°C, a pressure of 0.1-1 MPa, and a time of 2-12 h.

[0048] In this invention, the mass ratio of the fluorinated heterocyclic olefin monomer to the fluorosulfonic acid ether monomer is 0.05-5:1. Such a ratio is more conducive to the reaction. Preferably, the mass ratio of the fluorinated heterocyclic olefin monomer to the fluorosulfonic acid ether monomer is 0.5-2:1.

[0049] In this invention, when the fluorinated monoolefin monomer is in the gaseous state under reaction conditions, its injection rate is sufficient to maintain a reaction system pressure of 0.1-5 MPa. Alternatively, when the fluorinated monoolefin monomer is in a liquid state under reaction conditions, the amount added is 10% to 60% of the total mass of the reactants. The total weight of the monomers is the sum of the weights of the fluorinated monoolefin monomer, the fluorinated heterocyclic olefin monomer, and the fluorosulfonic acid ether monomer.

[0050] In some preferred embodiments of the present invention, the amount of the initiator is 0.01-2 wt% of the total weight of the liquid monomers (the sum of the weights of the liquid fluorinated monoolefin monomers, fluorinated heterocyclic olefin monomers, and fluorosulfonic acid ether monomers).

[0051] Within this dosage range, it is more conducive to initiating the copolymerization reaction, and the monomer conversion rate is high and the reaction rate is fast.

[0052] Preferably, the amount of the initiator is 0.05-1 wt% of the total weight of the liquid monomer.

[0053] In some preferred embodiments of the present invention, the initiator comprises an inorganic peroxide initiator. Preferably, the initiator comprises ammonium persulfate.

[0054] In this invention, preferably, the copolymerization reaction is a free radical emulsion polymerization reaction.

[0055] In some preferred embodiments of the present invention, in the free radical emulsion polymerization reaction, the emulsifier is selected from at least one of perfluoroalkyl carboxylates, perfluoroalkyl sulfonates, perfluoroalkoxy sulfonates and perfluorooctanoates. Preferably, the emulsifier is selected from perfluorooctanoates, and more preferably ammonium perfluorooctanoate.

[0056] Preferably, the amount of emulsifier used in the free radical emulsion polymerization reaction is 0.01-5 wt% of the mass of the solvent used in the polymerization reaction. More preferably, it is 0.5-2 wt%.

[0057] In some preferred embodiments of the present invention, after the free radical emulsion polymerization reaction is completed, the preparation method further includes precipitation, impurity removal, hydrolysis, acidification and drying of the copolymer emulsion.

[0058] In some preferred embodiments of the present invention, the precipitation treatment includes precipitating the copolymer emulsion obtained after the reaction using water and concentrated sulfuric acid.

[0059] In some preferred embodiments of the present invention, after precipitation treatment, the precipitated polymer is filtered and washed to remove impurities.

[0060] In some preferred embodiments of the present invention, the hydrolysis-acidification method includes: hydrolysis treatment using an alkaline solution, followed by acidification treatment using an acid solution.

[0061] A third aspect of the present invention provides a membrane electrode assembly, wherein the membrane electrode assembly includes a proton exchange membrane and a catalyst layer disposed on one side surface of the proton exchange membrane; the catalyst layer includes the aforementioned fluorosulfonic acid resin and a catalyst dispersed in the fluorosulfonic acid resin.

[0062] In this invention, the catalyst in the catalyst layer can be selected according to application requirements. For example, it may include platinum-based catalysts or iridium-based catalysts.

[0063] In some preferred embodiments of the present invention, the thickness of the catalyst layer and the mass percentage of the fluorosulfonic acid resin in the catalyst layer can be selected according to the application scenario. The thickness of the catalyst layer can be 1 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 10 μm, 15 μm, or any value between therewith. For example, the mass percentage of the fluorosulfonic acid resin in the catalyst layer can be 5%, 10%, 15%, 20%, 25%, 35%, 45%, or any value between therewith.

[0064] In this invention, the preparation method of the membrane electrode assembly can be conventional. For example, the fluorosulfonic acid resin, catalyst, and solvent can be mixed to form a slurry and then coated onto the proton exchange membrane.

[0065] In this invention, the mass percentage of the fluorosulfonic acid resin in the slurry can be selected according to the application scenario. For example, the mass percentage of the fluorosulfonic acid resin in the slurry can be 0.3%, 0.5%, 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, 2.2%, 2.5%, 3.0%, 5.0%, 8%, 15%, or any value between these values.

[0066] The solvent in the slurry can be selected according to the application scenario, and may include water and / or alcohol.

[0067] The present invention can also provide an application of a membrane electrode assembly in the hydrogen energy industry.

[0068] In some preferred embodiments of the invention, the application includes using the membrane electrode assembly as a component of a proton exchange membrane fuel cell, or using the membrane electrode assembly as a component of a water electrolysis hydrogen production device.

[0069] The present invention will be described in detail below through embodiments.

[0070] In the following examples, crystallinity was characterized by X-ray scattering (copper target, scan rate 2° / min).

[0071] Ion exchange equivalent EW: The potentiometric titration method is used; the equivalent mass EW = 1 / IEC; where IEC is the ion exchange capacity, which is equal to the number of moles of hydroxide ions consumed per gram of resin during the titration process, in mmol / g.

[0072] The mass percentage of the third repeating unit is obtained by dividing the molar mass of the third unit by EW. The mass percentage of the first repeating unit: If it is gaseous, the amount of monomer consumed from the start to the end of the reaction is recorded by a gas flow meter, and the mass percentage of the first repeating unit is obtained by dividing the amount consumed by the total mass of the product; if it is liquid, the mass percentage of the first repeating unit is calculated by measuring the remaining mass of the first repeating unit after the reaction is completed by gas chromatography.

[0073] The mass percentage of the second repeating unit is 1 - the mass percentage of the first repeating unit - the mass percentage of the third repeating unit.

[0074] The air permeability test method is as follows: A 50μm membrane of resin is prepared, and its oxygen permeability is tested using a differential pressure gas permeation analyzer. The oxygen heating and humidification conditions are 70℃ and 90%RH. Referring to the test standard GB / T20042.3-2022, the air permeability is calculated as the volume of gas passing through a unit thickness and unit area of ​​sample per unit time, with units in cm³. 3 ·cm / (cm 2 ·s·MPa).

[0075] The method for testing proton conductivity is as follows: a 50 μm membrane is made of resin and its proton conductivity is tested in pure water at 25 °C using the four-probe method. The unit is mS / cm.

[0076] The tensile strength test method is as follows: the resin is made into a 50μm film, and the tensile strength is measured using a tensile tester according to the method specified in GB / T20042.3-2022. The unit is MPa.

[0077] The electrochemical performance testing method is as follows: The resin is dissolved in a water-alcohol mixed solvent (the mass ratio of isopropanol to water is approximately 1:1) and mixed evenly with the iridium oxide catalyst to form a slurry (the weight ratio of resin to iridium oxide catalyst is 0.25), with a solid content of 1%; this slurry is coated on one side of the N115 proton exchange membrane to form an anode catalyst layer with a thickness of approximately 5 μm; the other side of the proton exchange membrane is coated with a slurry containing resin and platinum-carbon (slurry formulation: the mass ratio of isopropanol to water is 1:1, the solid content is 1%, the platinum-carbon ratio is 0.5, the weight ratio of resin to platinum is 0.7, and the thickness is 10 μm) to form a cathode catalyst layer, thus obtaining the water electrolysis hydrogen production membrane electrode, and its IV curve is obtained by steady-state polarization testing.

[0078] Example 1 This embodiment provides a perfluorosulfonic acid resin and a membrane electrode prepared therefrom.

[0079] The perfluorosulfonic acid resin is prepared according to the following method: Add 50g of the compound shown in formula (1-1) (w = 1, v = 1, X = F) and 50g of the compound shown in formula (2-1) (R5, R6, R7, R8 are all CF3, Y and Z are all S, m and n = 1) to a 500mL reactor. Then add 300mL of deionized water, 3g of ammonium perfluorooctanoate, and 1g of ammonium persulfate. After evacuating and replacing the nitrogen gas three times, evacuate again and fill the reactor with tetrafluoroethylene gas (R1, R2, R3, R4 are F) until the pressure inside the reactor reaches 0.5MPa. Turn on the stirrer and raise the temperature to 60℃ to initiate the polymerization reaction. Continuously introduce tetrafluoroethylene monomer to maintain the pressure inside the reactor at 0.5MPa. After reacting for 6 hours, stop heating and transfer the reaction solution to a beaker. Add 200mL of deionized water and 5mL of concentrated sulfuric acid to precipitate the polymer. Filter the precipitated polymer and wash it three times with deionized water to remove impurities. Hydrolysis was performed using NaOH aqueous solution (80℃, 2h); acidification was performed using H2SO4 aqueous solution (80℃, 2h). The resin was then dried in a hot air dryer at 90℃ for 24 hours, followed by drying at 120℃ for 5 hours to obtain perfluorosulfonic acid resin.

[0080] Equation (1-1) Equation (2-1) .

[0081] The potentiometric titration (EW) of the resin was determined to be 1089 g / mol, indicating that the mass percentage of the third repeating unit was 41.0%. In this embodiment, the weight percentages of the first, second, and third repeating units in the perfluorosulfonic acid resin were 28.7%, 30.3%, and 41%, respectively.

[0082] The crystallinity of this resin was tested using XRD, and the obtained curve is shown below. Figure 1 As shown. By Figure 1 It can be seen that there is an amorphous peak at around 15° and no crystalline peak at 17.5°, which proves that the resin has low crystallinity.

[0083] The resin was used to prepare a water electrolysis hydrogen production membrane electrode according to the test method described above, and its I / V performance was tested.

[0084] It is evident that the membrane electrode corresponding to this resin has good electrochemical performance, exhibiting a low voltage at a certain current density. In other words, when used for water electrolysis to produce hydrogen, the amount of electricity required to produce each kilogram of hydrogen is relatively low.

[0085] Example 2 The method of Example 1 was followed, except that the perfluoromonoolefin monomer was replaced with a hexafluoropropylene monomer (one of R1, R2, R3, and R4 is CF3, and the rest are F), and the amount used was such that the pressure inside the reactor was maintained at 0.5 MPa to obtain a perfluorosulfonic acid resin.

[0086] The potentiometric titration (EW) of the resin was determined to be 1122 g / mol, indicating that the mass percentage of the third repeating unit was 39.6%. In this embodiment, the weight percentages of the first, second, and third repeating units in the perfluorosulfonic acid resin were 25.2%, 35.2%, and 39.6%, respectively.

[0087] Example 3 The method of Example 1 was followed, except that 30g of the compound shown in formula (1-3) (w is 0, v is 1, X is F) was used as the fluorosulfonic acid ether monomer to obtain the perfluorosulfonic acid resin.

[0088] Equation (1-3) .

[0089] The potentiometric titration (EW) of the resin was determined to be 960 g / mol, indicating that the mass percentage of the third repeating unit was 29.3%. In this embodiment, the weight percentages of the first, second, and third repeating units in the perfluorosulfonic acid resin were 37.4%, 33.3%, and 29.3%, respectively.

[0090] Example 4 The method is the same as in Example 1, except that the perfluoromonoolefin monomer is replaced with 50g of perfluoro1-heptene monomer (one of R1, R2, R3, and R4 is C5F). 11 The remainder (F) was added to the reactor along with other monomers, and nitrogen gas was used to maintain the pressure inside the reactor at 0.5 MPa to obtain perfluorosulfonic acid resin.

[0091] The potentiometric titration (EW) of the resin was determined to be 1275 g / mol, indicating that the mass percentage of the third repeating unit was 34.8%. In this embodiment, the weight percentages of the first, second, and third repeating units in the perfluorosulfonic acid resin were 32.3%, 32.9%, and 34.8%, respectively.

[0092] Example 5 The method of Example 1 is followed, except that the perfluoromonoolefin monomer is replaced with a perfluoro2-butene monomer (R1 and R4 are CF3, and R2 and R3 are F), and the amount used is such that the pressure inside the reactor is maintained at 0.5 MPa to obtain perfluorosulfonic acid resin.

[0093] The potentiometric titration (EW) of the resin was determined to be 1135 g / mol, indicating that the mass percentage of the third repeating unit was 39.1%. In this embodiment, the weight percentages of the first, second, and third repeating units in the perfluorosulfonic acid resin were 27.4%, 33.5%, and 39.1%, respectively.

[0094] Example 6 Following the method of Example 1, except that 50g of the compound shown in formula (1-4) (R5 and R8 are both CF3, R6 is C3F7, R7 is C2F5, Y and Z are both S, m and n are 1) was used as the fluorinated heterocyclic olefin monomer to obtain perfluorosulfonic acid resin.

[0095] Equation (1-4) .

[0096] The potentiometric titration (EW) of the resin was determined to be 1072 g / mol, indicating that the mass percentage of the third repeating unit was 41.4%. In this embodiment, the weight percentages of the first, second, and third repeating units in the perfluorosulfonic acid resin were 25.9%, 32.7%, and 41.4%, respectively.

[0097] Comparative Example 1 Following the method of Example 1, except that the compound shown in formula (2-1) is not added, perfluorosulfonic acid resin is obtained.

[0098] The EW of the resin was determined to be 1040 g / mol by potentiometric titration, which indicates that the mass percentage of the third repeating unit was 42.7%.

[0099] In this comparative example, the perfluorosulfonic acid resin contains structural units derived from tetrafluoroethylene and those derived from... The weight percentages of the structural units were 57.3% and 42.7%, respectively.

[0100] The crystallinity of this resin was tested using XRD, and the obtained curve is shown below. Figure 1 As shown, it exhibits a distinct crystallization peak at 17.5°, indicating that the crystallinity of this resin is higher than that of the resin in Example 1.

[0101] The resin was fabricated into a water electrolysis hydrogen production membrane electrode according to the method described above, and its I / V performance was tested. At the same current density, its voltage was higher, for example, at 2 A / cm². 2 At the specified current density, the membrane electrode corresponding to the resin in Comparative Example 1 has a voltage approximately 30 mV higher than that in Example 1, which is equivalent to an additional 0.8 kWh of electricity consumed to produce each kilogram of hydrogen (calculated using the formula...). Where ηF≈0.98, U2-U1=0.029V≈0.03V=30mV).

[0102] Comparative Example 2 The difference from Example 1 is that after replacing the air with nitrogen, nitrogen is continued to be introduced until the pressure reaches 0.5 MPa, and no more perfluoromonoolefin monomers are introduced to obtain perfluorosulfonic acid resin.

[0103] The potentiometric titration (EW) of the resin was determined to be 942 g / mol, indicating that the mass percentage of the third repeating unit was 47.1%. The perfluorosulfonic acid resin in this comparative example was derived from... Structural units, derived from The weight percentages of the structural units were 52.9% and 47.1%, respectively.

[0104] Comparative Example 3 The difference from Example 1 is that formula (1-1) is replaced with 50g. Equation (2-1) is replaced with 50g. Perfluorosulfonic acid resin was obtained.

[0105] The potentiometric titration (EW) of the resin was determined to be 1016 g / mol, indicating that the mass percentage of the third repeating unit was 38.8%. The perfluorosulfonic acid resin in this comparative example was derived from... Structural units, derived from The weight percentages of the structural units and the structural units derived from tetrafluoroethylene are 38.8%, 24.7% and 36.5%, respectively.

[0106] The crystallinity of this resin was tested using XRD, and the obtained curve is shown below. Figure 1 As shown. Although the resin in Comparative Example 3 also showed no crystallization peak at 17.5°, its performance was still inferior to that of the embodiments of the present invention.

[0107] Fitting Figure 1 The XRD curves show that the crystallinity of Example 1, Comparative Example 1, and Comparative Example 3 of the present invention is approximately 7.67%, 40.66%, and 9.94%, respectively.

[0108] The resin of Comparative Example 3 was used to prepare a water electrolysis hydrogen production membrane electrode according to the test method described above, and its I / V performance was tested. At the same current density, its voltage was higher, for example at 2 A / cm². 2 At the current density, the membrane electrode corresponding to the resin in Comparative Example 3 is about 15 mV higher than that in Example 1, which is equivalent to consuming 0.4 kWh more electricity to produce each kilogram of hydrogen.

[0109] The performance test results of the above embodiments and comparative examples are summarized in Table 1.

[0110] Table 1

[0111] As can be seen from the results in Table 1, the perfluorosulfonic acid resin with the structural design of the present invention has significantly better performance, with good air permeability, while its mechanical properties and proton conductivity can be maintained at a good level.

[0112] Compared to Example 1, Example 2 uses hexafluoropropylene monomer, whose derived repeating unit has a side chain and has a good synergistic effect with other repeating units, thus improving its oxygen permeability and air permeability.

[0113] Example 3 differs from Example 1 in that it uses a different type of perfluorosulfonic acid ether monomer, with w being 0 and v being 1. The repeating unit derived from the perfluorosulfonic acid ether monomer in Example 1 has more suitable side groups, which can better provide proton conduction sites and also provide a larger free volume. Therefore, the resin of Example 1 has better air permeability than that of Example 3.

[0114] Example 4: Due to the long side chains on the monoolefin monomer, the oxygen permeability, tensile strength, and proton conductivity all decreased slightly. Example 5: Due to the large number of side chains, the tensile strength decreased compared to Example 1. Example 6: Due to the long-chain substituents on the fluorinated heterocyclic olefin monomer, the oxygen permeability and proton conductivity decreased.

[0115] Comparative Example 1, lacking the sulfur-containing heterocyclic structure of this invention, exhibits significantly reduced air permeability and cannot be used as a breathable resin. Comparative Example 2, lacking the perfluoromonoolefin monomer, shows reduced mechanical strength and oxygen permeability, as the perfluoromonoolefin monomer in this invention also contributes to air permeability in the resin. Comparative Example 3, employing a heterocyclic structure outside the scope of this invention, also exhibits poor air permeability.

[0116] The I / V performance data is listed in Table 2.

[0117] Table 2

[0118] As can be seen from Table 2, the membrane electrode corresponding to the resin of the present invention has good electrochemical performance and has a low voltage at a certain current density. That is to say, when it is used to produce hydrogen by electrolysis of water, the amount of electricity required to produce each kilogram of hydrogen is low.

[0119] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combining the various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A fluorosulfonic acid resin, characterized in that, The fluorosulfonic acid resin includes a first repeating unit shown in Formula I, a second repeating unit shown in Formula II, and a third repeating unit shown in Formula III; Formula I; Formula II; Formula III; Among them, R1, R2, R3, and R4 are each independently a straight-chain or branched fluorinated alkyl group of F or C1-C7. R5, R6, R7, and R8 are each independently an F or C1-C3 fluoroalkyl group; at least one of Y or Z is S, n is 1 or 2, and m is 0 or 1; R9, R 10 Each is independently an F or C1-C3 fluorinated alkyl group; w is an integer between 0 and 5, v is an integer between 0 and 5, w and v are not both 0, and X is F, Cl or OM; M is H or an alkali metal; a, b, and c represent the number of repeating units, each of which is an integer.

2. The fluorosulfonic acid resin according to claim 1, wherein, In Formula I, three of R1, R2, R3, and R4 are F, and the remaining one is a C1-C4 straight-chain or branched perfluoroalkyl group.

3. The fluorosulfonic acid resin according to claim 2, wherein, In Formula I, three of R1, R2, R3, and R4 are F, and the remaining one is a C1-C4 straight-chain perfluoroalkyl group.

4. The fluorosulfonic acid resin according to claim 1 or 2, wherein, In Equation II, m is 1; And / or, in Equation II, Y and Z are both S; And / or, in Equation II, R5, R6, R7, and R8 are each independently F or CF3.

5. The fluorosulfonic acid resin according to claim 4, wherein, In Equation II, m is 1 and n is 1.

6. The fluorosulfonic acid resin according to claim 1 or 2, wherein, In Equation III, w is 0 or 1, and v is 1 or 2; And / or, in Formula III, X is OH.

7. The fluorosulfonic acid resin according to claim 1 or 2, wherein, R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 All are selected from F or perfluorinated alkyl groups.

8. The fluorosulfonic acid resin according to claim 1 or 2, wherein, Based on the total weight of the fluorosulfonic acid resin, the content of the first repeating unit is 10-60%, the content of the second repeating unit is 10-60%, and the content of the third repeating unit is 10-70%.

9. The fluorosulfonic acid resin according to claim 8, wherein, Based on the total weight of the fluorosulfonic acid resin, the content of the first repeating unit is 25-35%, the content of the second repeating unit is 25-40%, and the content of the third repeating unit is 30-50%.

10. The fluorosulfonic acid resin according to claim 1 or 2, wherein, The ion exchange equivalent of the fluorosulfonic acid resin is 700-1500 g / mol.

11. The fluorosulfonic acid resin according to claim 10, wherein, The ion exchange equivalent of the fluorosulfonic acid resin is 1000-1200 g / mol.

12. A method for preparing a fluorosulfonic acid resin, characterized in that, The preparation method includes: In the presence of an initiator and a solvent, fluorinated monoolefin monomers, fluorinated heterocyclic olefin monomers, and fluorinated sulfonic acid ether monomers are copolymerized to obtain fluorinated sulfonic acid resins. The fluorinated monoolefin monomer includes The fluorinated heterocyclic olefin monomer includes The fluorosulfonic acid ether monomer includes ; Among them, R1, R2, R3, and R4 are each independently a straight-chain or branched fluorinated alkyl group of F or C1-C7. R5, R6, R7, and R8 are each independently an F or C1-C3 fluoroalkyl group; at least one of Y or Z is S, n is 1 or 2, and m is 0 or 1; R9, R 10 Each is independently an F or C1-C3 fluorinated alkyl group; w is an integer between 0 and 5, v is an integer between 0 and 5, w and v are not both 0, and X is F, Cl or OM; M is H or an alkali metal; a, b, and c represent the number of repeating units, each of which is an integer.

13. The method for preparing the fluorosulfonic acid resin according to claim 12, wherein, The copolymerization reaction is carried out at a temperature of 40-120℃, a pressure of 0.1-5MPa, and a time of 2-48h. And / or, the copolymerization reaction is a free radical emulsion polymerization reaction; And / or, the amount of the initiator is 0.01-2 wt% of the total weight of the liquid monomers, wherein the total weight of the liquid monomers is the sum of the weights of the liquid fluorinated monoolefin monomers, fluorinated heterocyclic olefin monomers, and fluorinated sulfonic acid ether monomers.

14. The method for preparing the fluorosulfonic acid resin according to claim 13, wherein, In the free radical emulsion polymerization reaction, the amount of emulsifier used is 0.01-5 wt% of the mass of the solvent used in the polymerization reaction.

15. The method for preparing the fluorosulfonic acid resin according to claim 12 or 13, wherein, The mass ratio of the fluorinated heterocyclic olefin monomer to the fluorinated sulfonic acid ether monomer is 0.05-5:1; When the fluorinated monoolefin monomer is in the gaseous state under reaction conditions, its injection rate is sufficient to maintain a reaction system pressure of 0.1-5 MPa. Alternatively, when the fluorinated monoolefin monomer is in a liquid state under reaction conditions, the amount added is 10% to 60% of the total weight of the monomer, wherein the total weight of the monomer is the sum of the weights of the fluorinated monoolefin monomer, the fluorinated heterocyclic olefin monomer, and the fluorinated sulfonic acid ether monomer.

16. The method for preparing the fluorosulfonic acid resin according to claim 15, wherein, The mass ratio of the fluorinated heterocyclic olefin monomer to the fluorinated sulfonic acid ether monomer is 0.5-2:

1.

17. A membrane electrode assembly, characterized in that, The membrane electrode assembly includes a proton membrane and a catalyst layer disposed on one side surface of the proton membrane; the catalyst layer includes a fluorosulfonic acid resin and a catalyst dispersed in the fluorosulfonic acid resin. The fluorosulfonic acid resin is the fluorosulfonic acid resin according to any one of claims 1-11, or the fluorosulfonic acid resin prepared by the preparation method according to any one of claims 12-16.